Blender compositing and post processing : learn the techniques required to create believable and stunning visuals with Blender Compositor - Vepakomma, Mythravarun (Community experience distilled., 2014)
This book is a step-by-step compositing guide, with lots of illustrations and practical approaches and implementations to attain a desired visual quality to a deadline. Each chapter progressively adds to your skillset, covering a wide range of CG film making compositing concepts. This book is for digital CG artists looking to add photo realism and life to their footage. This book also assists technical CG artists in strategizing and implementing productive lighting. If you are new to Blender or compositing, this book will guide you step by step in gaining compositing skills.